Keteladanan Spiritual dalam Kepemimpinan Yosua: Pengaruhnya dalam Meningkatkan Ketekunan Rohani dalam Konteks Kepemimpinan - Gerbin Tamba; Sarwedy Nainggolan; Janes Sinaga; Juita Lusiana Sinambela (PT. Penerbit Tiga Mutiara, 2023)
This study aims to analyze the concept of spiritual example in Joshua's leadership and its impact on increasing spiritual perseverance in the context of leadership. This study uses a qualitative method with a literature review approach to explore the concept of spiritual example in Joshua's leadership and how this concept influences the increase of spiritual perseverance in the context of leadership. Through analysis of religious, theological, and leadership literature, this study reveals that Joshua, an ancient leader in the Bible story, represents a spiritual role model in leadership roles. Joshua's leadership characteristics that reflected spiritual values, such as integrity, firm faith, and commitment to moral goals, had a positive impact in guiding the Israelites and strengthening spiritual perseverance in the face of challenges. This study describes how Joshua's spiritual example inspires and guides community members to follow the spiritual values he exhibits. Furthermore, the implication of the concept of spiritual example in leadership is the potential to strengthen the moral and ethical foundations in leadership roles. This research also shows the importance of the spiritual dimension in forming meaningful and authentic leadership characters in dealing with modern dynamics. The results of this study have significant practical implications for contemporary leaders. An understanding of the concept of spiritual example in Joshua's leadership can help leaders integrate spiritual values into their leadership practices. As such, this research makes a valuable contribution to understanding the relationship between spiritual example, spiritual perseverance, and meaningful leadership in this complex world.